2013
DOI: 10.1002/wsb.318
|View full text |Cite
|
Sign up to set email alerts
|

Habitat use by spruce grouse in northern Wisconsin

Abstract: Spruce grouse (Falcipennis canadensis) habitat use varies widely across their range and is not well-understood near the southern extent of their range. Threats to conifers from climate change make understanding habitat use at the southern edge of the range increasingly important. We obtained habitat information on 55 radiocollared spruce grouse in northern Wisconsin, USA from 16 May 2007 to 10 July 2012. Black spruce (Picea mariana) and tamarack (Larix laricina) were the most common habitat components. Some of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…For the purposes of our study, we restricted the sampling frame to lands managed by the state and by the United States Forest Service, which included the Superior National Forest. Spruce Grouse use various ages of forest throughout their range; earlier successional stages have been reported to be important in the western United States (Schroeder et al ), mid‐successional forest was reported as important in New York (Ross et al ), and mature forest was important in Wisconsin (Anich et al ). We suspected this variability was due to differences in forest structure rather than age, so we included all stand ages except those identified for harvest in the next five years and those harvested in the past five years.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the purposes of our study, we restricted the sampling frame to lands managed by the state and by the United States Forest Service, which included the Superior National Forest. Spruce Grouse use various ages of forest throughout their range; earlier successional stages have been reported to be important in the western United States (Schroeder et al ), mid‐successional forest was reported as important in New York (Ross et al ), and mature forest was important in Wisconsin (Anich et al ). We suspected this variability was due to differences in forest structure rather than age, so we included all stand ages except those identified for harvest in the next five years and those harvested in the past five years.…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, we used timber harvest data (U.S. Forest Service ) and fire records (National Interagency Fire Center ) to identify and exclude recently harvested or burned stands. In 2014, we included forest types reported to be preferred by Spruce Grouse in this region, including jack pine, black spruce, and tamarack (Robinson , Pietz and Tester , Anich et al ). We also included white cedar ( Thuja occidentalis ), which was used, but not preferred, in Wisconsin (e.g., Anich et al ) because land managers in Minnesota believed that white cedar might be regionally important based on field observations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tirpak et al 2008;Zhou et al 2015a), vegetation type (e.g. Chávez-león et al 2004;Dzialak et al 2011;Anich et al 2013) and climate change (e.g. Kvasnes et al 2014).…”
Section: Macroscopic Ecologymentioning
confidence: 99%
“…Protection of black spruce forests will likely allow the persistence of Boreal Chickadee, Spruce Grouse, and other archetypal boreal species in these hemiboreal forests of Minnesota. However, habitat needs of these permanent resident species likely vary throughout the year and other tree species associations could be important at certain times, e.g., Spruce Grouse use of tamarack during summer months in Wisconsin (Anich et al 2013). …”
Section: Species Of Greatest Conservation Needmentioning
confidence: 99%